Physical Literacy for life: the facts, the trends, and the effects - Fabiano Henrique Rodrigues Soares (Global Journal of Obesity, Diabetes and Metabolic Syndrome - Peertechz Publications, 2020)
As sedentary related cardiometabolic outcomes have increased worldwide for the past decades, stimulating a physically active lifestyle among younger populations is imperative. Physical education, as a key tool to develop physical literacy (PL), can reverse this global trend using different approaches. Observational and experimental research must be conducted to address the multidimensional aspects of PL. This proposal aims to prepare, conduct research and present results about affective, physical, cognitive and behavioral aspects PL. There should be a commitment to attracting, developing, and supporting outstanding undergraduate and graduate students and postdoctoral fellows through interdisciplinary research and interaction with the private and public sectors. The aim is to promote knowledge for diverse communities so they can understand the importance of PL and can make better decisions regarding physical activity throughout life.